Sustainability Reporting and Financial Performance: The Mediating Role of CEO Characteristics and Ownership Structure - Sabaruddinsah, Sabaruddinsah; Asiah, Neng (Lentera Ilmu Nusantara, 2025)
This study analyzes the transformation mechanism of sustainability reporting into financial performance through the mediating role of CEO characteristics (education and tenure) and ownership structure. This study addresses the paradox in the context of non-cyclical consumer sector companies in Indonesia, where increasing adoption of sustainability reporting is accompanied by a decline in financial performance. This explanatory quantitative study used 145 observations from non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 software, which included evaluation of the measurement and structural models with a bootstrapping procedure of 5,000 samples to test the significance of the mediation effect. Sustainability reporting was shown to have a significant effect on financial performance. However, more crucially, CEO characteristics and ownership structure significantly mediated this relationship. The model showed good predictive relevance and goodness of fit. These findings provide theoretical contributions by integrating Stakeholder Theory, Upper Echelons Theory , and Agency Theory into a cohesive mediation framework. Practically, this research provides guidance for boards of commissioners in the leadership succession process and corporate governance design to maximize the value of sustainability investments. This research shifts the analytical paradigm from a moderation to a mediation approach, revealing the